Огляд досліджень Bacillariophita в Українському Поліссі. ІI - Бухтіярова, Л.М. (Український ботанічний журнал, 2009)
Систематизированы результаты исследований диатомовых водорослей в Украинском Полесье (УП), которое занимает около 20 % территории Украины, имеет разветвленную гидрологическую сеть, многочисленные охраняемые природные объекты. На основе оригина льных и литературных данных от начала исследований Bacillariophyta в конце ХІХ ст. до настоящего времени впервые составлен систематический список таксонов, за регистрированных в УП. Список Васіllariophyta в УП отвечает современной таксономии отдела и насчитывает 544 вида (651 внутривидовой таксон, включая номенклатурный тип видов). За последние 35 лет в УП зарегистрированы 74 вида (77 внутривидовых таксонов, включая номенклатурный тип видов), пополнивших альгофлору Украины. Во второй части обзора обсуждается изученность, распределение и таксономические особенности Васіl la riophyta в Житомирском, Киевском, Черниговском и Новгород-Северском Полесье, а также для УП в целом. Investigations of the diatoms are systematized for Ukrainian Polissya (UP), occupying about 20 % of Ukraine’s area. UP possesses the most developed hydrological network in Ukraine and has numerous natural units of different protection status. A taxonomic list of Васіllariophyta taxa recorded in UP is compiled for the first time based of the original and literature data from the beginning of the diatom investigations of UP in the end of ХІХ century until present. The list of Васіllariophyta in UP corresponds to the modern taxonomy of the division and includes 544 species (651 infraspecific taxa, including nomenclatural types of the species). For the past 35 years, there were 74 diatomspecies (77 infraspecific taxa) recorded in UP as an additional contribution to the algoflora of Ukraine. In the second part of the review, a comparison of study state, distribution, and taxonomic cha racteristics of Васіllariophyta within Zhytomyr, Kyiv, Chernigiv, Novgorod-Siversky Polissya, and for UP in general, are discussed.